Measuring the level of health awareness among high school students Aqeel Najm Abd (Journal of the College of Basic Education, 2022)
The aim of the search measuring the levl of health awarenes among high school students andidentify th significance of difference inthe level of health awarenes according to variables (gender, specialization, grade), to achieve the aims the researcher adopted a health awareness scale (Mohammad, 2007) which consisted of (30 items) in the from of report phrases and putting in front of each items graded variables for answering are (Apply to me perfectly, apply to fairly, do not apply to completely) given them marks (3, 2, 1) to items whith measurement health awareness and reflects the correcting (1, 2, 3) of the formed items reverse the measurement health awareness, the veracity of the scale was verified through apparent honesty and verification of stability through the use of the Alpha Kronbach formula, The measurement was applied on a researech sample of (200) students were selected style class random, and data were analyzed by using the Statistical tools SPSS, The results showed that the level of health awareness was low among high school students, The results showed no statistically significant differences in health awareness due to variables (gender, specialization, grade), In light of the results the searcher presented a set of conclusions, recommendations and suggestions.